Vole Abundance in Agricultural Lands of Ukraine: Analysis Based on Archives of the Middle 20th–Early 21st Centuries - Mezhzherin , S. V.; Rashevska, A. V.; Potopa , A. V. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2025)
The research on the spatial distribution and long-term dynamics of the voles Microtus arvalis (Pallas, 1778), M. levis Miller, 1908, M. socialis (Pallas, 1773) in agricultural landscapes of Ukraine was carried out using the census data of the State Plant Protection Inspection Service during 1948–2006. It revealed that the maximum density of colonies and regular abundance outbreaks occurred in Western and North-Western regions and the Forest-Steppe zone of Right-bank Ukraine. These areas either only supported M. arvalis or this species significantly dominated over M. levis. The low abundance with relatively stable populations was reported from the Left-bank Steppe oblasts, occupied by M. levis and M. socialis. Two main changes in abundance are distinguished over time. The first was a dramatic increase throughout Ukraine in the 1980s when a considerable part of arable lands were used for plantations of perennial grasses, and the second was a gradual decrease, especially pronounced in western oblasts of Ukraine among populations of M. arvalis. The comparison of the average population parameters between the early period of research in 1948–1954 and its final stages in 2000–2006, indicates a 2.8-fold decrease in the number of inhabited burrows. Given the additional circumstances, the decrease could be even higher, 5–8 or even 10 times. This reduction is mainly associated with the loss of meadow ecosystems. The population decline and the absence of mass reproduction in agroecosystems of voles provide a basis for prohibiting rodenticides in fields.